The Separation of AHF from Fibrinogen. II - van Creveld, S; Veder, H. A; Pascha, C. N (Thrombosis and Haemostasis, 1960)
A number of experiments, aimed at a greater yield of human AHF in the chromatographic separation of fibrinogen and AHF, are reported. The experiments were conducted with both anion- and cation exchangers on a basis of cellulose, and at different pH’s. Good results were obtained with ECTEOLA-cellulose, although for therapeutical purposes a somewhat greater yield would be preferable and for the determination of the properties and constitution of AHF the preparations are not pure enough. Further work is in progress.